2020
DOI: 10.1155/2020/7136160
|View full text |Cite
|
Sign up to set email alerts
|

GLIDE: A Game Theory and Data-Driven Mimicking Linkage Intrusion Detection for Edge Computing Networks

Abstract: The real-time and high-continuity requirements of the edge computing network gain more and more attention because of its active defence problem, that is, a data-driven complex problem. Due to the dual constraints of the hybrid feature of edge computing networks and the uncertainty of new attack features, implementing active defence measures such as detection, evasion, trap, and control is essential for the security protection of edge computing networks with high real-time and continuity requirements. The basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…Li et al [ 36 ] proposed a data-based mimetic intrusion detection game model called GLIDE as a defense against intrusion attacks for edge computing networks, combining a strategy of multi-redundancy voting algorithms to optimize their intrusion detection rate at edge computing network terminals and game theory. The model was designed to establish a measure to detect and eliminate intrusion attacks in complex environments for edge computing networks because they are characterized by having ambiguous interconnections.…”
Section: State Of the Artmentioning
confidence: 99%
“…Li et al [ 36 ] proposed a data-based mimetic intrusion detection game model called GLIDE as a defense against intrusion attacks for edge computing networks, combining a strategy of multi-redundancy voting algorithms to optimize their intrusion detection rate at edge computing network terminals and game theory. The model was designed to establish a measure to detect and eliminate intrusion attacks in complex environments for edge computing networks because they are characterized by having ambiguous interconnections.…”
Section: State Of the Artmentioning
confidence: 99%
“…In this case, the base station will encourage CRs to offload their tasks to the nearby CPs through energy-efficient Mathematical Problems in Engineering D2D links. Of course, users can also choose to perform their tasks locally [32]. e available spectrum in this single-cell system is divided into N orthogonal subchannels, and the bandwidth of each subchannel is w. Each D2D link will be assigned an OFDMA subchannel.…”
Section: System Modelingmentioning
confidence: 99%
“…(1) Local Computing. f l r is used to represent the computing power of r (such as the amount of data the device can process per second), and different CRs have different computing power [32]. According to the task's parameter set, the execution time of the r local computing task can be expressed as…”
Section: Calculation Modelmentioning
confidence: 99%
“…Experiments prove that the classification performance is better than other classification algorithms. Qianmu, Jun, & Shunmei, (2020) constructs WT models based on different forms of decision trees by using the idea of integration. It is found that WT integration models overcome the shortcomings of each sub-model and realize effective early warning of customer default.…”
Section: Introductionmentioning
confidence: 99%